2002
DOI: 10.1124/jpet.302.1.390
|View full text |Cite
|
Sign up to set email alerts
|

(E)-2(R)-[1(S)-(Hydroxycarbamoyl)-4-phenyl-3-butenyl]-2′-isobutyl-2′-(methanesulfonyl)-4-methylvalerohydrazide (Ro 32-7315), a Selective and Orally Active Inhibitor of Tumor Necrosis Factor-α Convertase

Abstract: Tumor necrosis factor-␣ (TNF-␣), a cytokine secreted by inflammatory cells, has been implicated in several inflammatory disease, is a potent, orally active inhibitor of the TNF-␣ convertase (TACE), an enzyme responsible for proteolytic cleavage of the membrane bound precursor, pro-TNF-␣. Ro 32-7315 inhibited a recombinant form of TACE (IC 50 ϭ 5.2 nM) with selectivity over related matrix metalloproteinases. In a cellular assay system, THP-1 cell line, and in human and rat whole blood, Ro 32-7315 significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…The importance of released TNF-a in this context was also shown by others using the unspecific metalloproteinase inhibitor Marimastat (Robinson et al, 2002). Applying the specific TACE inhibitor Ro32-7315 (Beck et al, 2002), we demonstrated that TACE activity is essential for autocrine TNF-a-stimulated MMP-9 expression. Slight impairment of MMP-9 gene expression was also observed upon blocking of TNF-R2, which may be caused by 'ligand passing' from TNF-R2 to TNF-R1.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The importance of released TNF-a in this context was also shown by others using the unspecific metalloproteinase inhibitor Marimastat (Robinson et al, 2002). Applying the specific TACE inhibitor Ro32-7315 (Beck et al, 2002), we demonstrated that TACE activity is essential for autocrine TNF-a-stimulated MMP-9 expression. Slight impairment of MMP-9 gene expression was also observed upon blocking of TNF-R2, which may be caused by 'ligand passing' from TNF-R2 to TNF-R1.…”
Section: Discussionsupporting
confidence: 82%
“…To investigate whether TACE, which is responsible for the release of TNF-a from the plasma membrane, is involved in basal MMP-9 secretion, THP-1 cells were treated with Ro32-7315, a highly specific inhibitor of TACE activity (Beck et al, 2002). Zymographic analysis of secreted enzymes showed that increasing concentrations of Ro32-7315 led to a decrease in MMP-9 release from the cells ( Figure 1E).…”
Section: Resultsmentioning
confidence: 99%
“…Although 100 ng/ml of bortezomib doubled the sCD30 release (707.5-1569 U/ml, Po0.0001) in ADAM10-defective cells with functional ADAM17, it failed to stimulate CD30 shedding in ADAM17-defective cells. We also applied the ADAM17-selective inhibitor, Ro32-7315 13 ( Figure 2b). It blocked bortezomib-stimulated sCD30 release from L540 cells with an IC 50 of approximately 230 nM.…”
Section: Resultsmentioning
confidence: 99%
“…Dot blot analysis shows the percentage of viable (lower lift) and apoptotic (upper and lower right) cells. 13.31% (upper right gate). These data confirm that induction of CD30 shedding by bortezomib substantially perturbs anti-CD30-targeted immunotherapy.…”
Section: Inhibition Of Adam17 Increases the Cytotoxicity Of Bortezomimentioning
confidence: 99%
See 1 more Smart Citation